EDUKASI MELALUI WEBINAR MENINGKATKAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI - Tarsikah Tarsikah; Nur Eva Aristina (Politeknik Kesehatan Kemenkes malang, 2022)
The COVID-19 emergency has narrowed the space for teenagers to get information and education about health. Easily accessible adolescent reproductive health education is very important because various research data shows adolescents are reluctant to have discussions with their parents regarding reproductive health problems. Objective: to increase adolescent knowledge about reproductive health during physical distancings. The method used is educational, participative and normative, through online activities with 4 meetings with adolescents in the village of Gunungrejo Singosari Malang. Prior to this, data was obtained: the average value of knowledge about reproductive health before (pre test) was in the good category (score 80), but there were still indicators of questions with sufficient value, namely knowledge of adolescent development and pre-conception preparation. After education through webinars, four times there was an increase in the knowledge score (score 89) with each item indicator categorized as good. Conclusion: community service in the form of health education through webinars can increase adolescent knowledge about reproductive health. Increased knowledge is expected to be followed by promotive behavior in the field of reproductive health.